Officially Supported Export Credits : Developments and Prospects - Jarvis, Christopher; Horvath, Balazs; Kuhn, Michael (Washington, D.C. : International Monetary Fund, 1995)
This study discusses the importance of export credits, their recent growth, and the trend toward more extensive reliance by official bilateral creditors on export credits as an instrument of financial support, and raises a number of issues regarding the role and limitations of export credit financing, espeically for economies in transition.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet